Characterization of the protozoa community observed in activated sludge of Braga wastewater treatment plant - Pereira, Ana Paula (2003)
Resumo apresentado em Environment 2010 : Situation and Perspectives for the European Union, 6-10 May 2003, Porto, Portugal.